Smartphone - An Aid to Healthcare Delivery or a Reservoir of Infection? - Indu Dinesh; Renuka Prithviraj (Rajiv Gandhi University of Health Sciences, 2024)
BackgroundAim The widespread use of mobile phones particularly smartphones in healthcare settings raises concerns about their potential to serve as vectors for nosocomial infections. This study aimed to estimate the proportion of infected mobile phones used by hospital staff in a tertiary care facility in Bengaluru and assess the pattern of contamination.Methods A cross-sectional study was conducted involving 400 healthcare providers including faculty students nurses and support staff who were surveyed about their mobile phone usage and hygiene practices. Swab samples were collected from participantsrsquo mobile phones and cultured for bacterial growth.Results Results revealed that 85 of participants used smartphones regularly at work. While 90 of participants were aware of hand hygiene guidelines 40 reported rarely or never cleaning their phones. Notably 82.25 of phones were found to be contaminated with Staphylococcus aureus being the most common pathogen isolated. Contamination levels varied among healthcare providers with faculty and postgraduate students showing the highest rates.Conclusion The study highlights the potential role of mobile phones as vectors for nosocomial infections in healthcare environments. Despite awareness of hygiene guidelines inadequate phone cleaning practices persist. The findings suggest that mobile phones could serve as reservoirs for harmful pathogens posing a risk not only within healthcare settings but also to the broader community. The study demands for the development of standardized disinfection protocols for mobile devices in hospitals to reduce the spread of infections.